EKSISTENSI PENGADILAN HAK ASASI MANUSIA DALAM PENEGAKAN HUKUM DI TIMOR TIMUR PASCA JAJAK PENDAPAT - Satrio Saptohadi (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Court of Human Rights is a special court below the General Court that located in the Regency/City which jurisdiction includes in its District Court. The authority of the Court of Human Rights is tasked to examine and rule on cases of human rights violations, investigate and adjudicate serious violations of human rights which heavily committed outside the territorial boundaries of the Republic of Indonesia by an Indonesian citizen. Court of Human Rights, which adjudicate cases of gross human rights violations in East Timor Polls Post-defendants have been executed by both military and civilian, and was decided by the Court of Human Rights under law No. 26 Year 2000 regarding Human Rights Court.Key words: court of human rights, violation of human rights, law enforcement